2020
DOI: 10.1097/eja.0000000000001290
|View full text |Cite
|
Sign up to set email alerts
|

Serratus anterior plane block for video-assisted thoracoscopic surgery

Abstract: BACKGROUND The serratus anterior plane block (SAPb) is a promising interfascial plane technique able to provide profound thoracic analgesia. As only a few studies with quite small patient samples are presently available, the analgesic efficacy of adding SAPb to general anaesthesia in video-assisted thoracoscopic surgery (VATS), compared with general anaesthesia only, remains unclear. OBJECTIVES Our primary aim was to assess the analgesic efficacy of SAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
4
35
0
1
Order By: Relevance
“…The outcomes of the SAPB may differ depending on the type, volume, concentration, and target point of the local anesthetic. In superficial or deep SAPB applications, 10-30 mL of 0.125%-0.375% ropivacaine or bupivacaine were administered and it was reported to provide adequate analgesia for rib fractures, VATS, thoracotomy, breast surgery [2,12,13]. In order to avoid the development of a winged scapula and local anesthetic systemic toxicity, we administered 20 mL of 0.25% bupivacaine by USG guidance to apply a deep SAPB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcomes of the SAPB may differ depending on the type, volume, concentration, and target point of the local anesthetic. In superficial or deep SAPB applications, 10-30 mL of 0.125%-0.375% ropivacaine or bupivacaine were administered and it was reported to provide adequate analgesia for rib fractures, VATS, thoracotomy, breast surgery [2,12,13]. In order to avoid the development of a winged scapula and local anesthetic systemic toxicity, we administered 20 mL of 0.25% bupivacaine by USG guidance to apply a deep SAPB.…”
Section: Discussionmentioning
confidence: 99%
“…In two meta-analyses investigating the analgesic efficacy of adding the SAPB to general anesthesia, the authors stated that combining the USG-guided SAPB with general anesthesia provides more effective postoperative analgesia in VATS [2,19]. They stated that combining the USGguided SAPB with general anesthesia provides more effective postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blanco et al reported for the first time that SAB block has a blocking effect on the intercostal nerve of T 2˜T9 and can provide chest wall and axillary regional anesthesia [9]. Previous studies have reported the effects of SAB blockers and placebos on opioid consumption in patients with breast cancer after modified radical mastectomy [13,14]. Recently, Yao et al [14]reported that pre-operative administration of SAB with ropivacaine improved the quality of recovery, postoperative analgesia, and patient satisfaction following breast cancer surgery, However, Fu jii et al [15] found that compared to SAB block, the PECS-2 block reduced chronic pain six months after MRM.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of SAPB and local infiltration anesthesia for postoperative analgesia after VATS found that patients in the SAPB group had better VAS scores during the first 8 h postoperatively, and the dose of opioids in SAPB group was far lower. 28 A recent meta-analysis by De Cassai et al 29 on the analgesic effect of SAPB in patients undergoing thoracoscopic surgery showed that general anesthesia combined with SAPB reduced perioperative pain compared with general anesthesia alone. The analgesic score in the SAPB group at 6-, 12-, and 24 hrs after surgery was lower than that of the control group, but the analgesic effect at 6 hrs was better than that at 24 hrs.…”
Section: Discussionmentioning
confidence: 99%